مشروعية الاندماج المصرفي في القانون العراقي - Sabry, Sameh; Mohammed, Akram (Journal of Legal Sciences, 2022)
The legality of banking merger is related to the impact that the merger process has on competition in the market. A merger (as one of the forms of economic concentration) can affect future competition or be misused to achieve purposes contrary to free and fair competition. Therefore, controlling economic concentration processes, including mergers, It would contribute to maintaining the spirit of competition between banks and achieving the greatest benefit from them on the one hand, and to avoid their damages on the other hand.